Early-life surface colonization with multi-drug resistant organisms in the neonatal intensive care unit - Loe, Marcus Wing Choy (2023)
Objectives: In this study, we aim to describe the patterns of early-life surface colonization with multi-drug resistant (MDR) organisms (MDROs) among newborns admitted to the neonatal intensive care unit (NICU). Methods: We conducted a retrospective descriptive study of infants with culture-positive external ear surface swabs performed immediately after admission to our NICU from January 1, 2017 – December 31, 2021. Clinical characteristics, culture and antibiotic susceptibility data were extracted from the department data collection and hospital electronic databases. Results: A total of 314 infants were included - median 34 weeks gestation (interquartile range [IQR] 30, 38) and median birthweight 2147 g (IQR 1470, 2875). Of the 379 bacterial isolates obtained, 259 (68.3%) were gram-negative with Escherichia coli (149/379, 39.3%) and Klebsiella spp (57/379, 15.0%) the most common gram-negatives isolated. MDROs accounted for 17.4% (45/259) of gram-negative isolates. There was no methicillin-resistant Staphylococcus aureus (0/22 isolates) or vancomycin-resistant Enterococcus (0/68) detected among isolates tested. A total of 27 (8.6%) infants developed bacteremia, of which 21/27 (77.8%) had concordant bacteria isolated from surface cultures, with identical resistance patterns, and 4/21 (19.0%) isolates were MDROs. Conclusion: In our setting where gram-negative bacteria accounted for a high proportion of initial colonization, MDR gram-negatives accounted for up to 17% of colonizing gram-negative bacteria detected.